High open-circuit voltage in lead sulfide quantum dot solar cells via solution-phase ligand exchange with low electron affinity cadmium halides - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Mitra, Anurag; Rath, Arup K. (JOURNAL OF MATERIALS CHEMISTRY A, 2023)
The deployment of colloidal quantum dots (QDs) in building high-performance solar cells and other optoelectronic applications relies on the passivation of unsaturated surface atoms through ligand engineering to attain a trap-free energy bandgap and strong QD coupling while maintaining the quantum confinement effect. Despite major advancements in surface passivation strategies, the open circuit voltage (V-oc) of lead sulfide (PbS) QD solar cells is limited by undesirable sub-bandgap states and high-bandtail states. The most advanced solution-phase ligand exchange strategy for PbS QDs depends on lead halide ligands, which improved the photocurrent and fill factor in QD solar cells significantly, but only an incremental change in V-oc is observed. Here we showcase a solution-phase hybrid ligand passivation strategy for PbS QDs using shallow electron affinity cadmium halide and thiol ligands. The cadmium halide ligand treatment results in the sub-monolayer substitution of surface Pb atoms by Cd atoms. The photophysical properties of QDs improve significantly to show intense band edge emission, diminished trap emission and reduced Urbach tail states. The photovoltaic devices built using cadmium halide-treated QDs show low reverse saturation current, which helps to attain a record 0.7 V V-oc (for a 1.28 eV bandgap) and 12.3% PCE.

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Solution-phase ligand engineering for all-quantum-dot near-infrared light-emitting diodes - Biswas, Arindam; Mitra, Anurag; Sharma, Ashish; Shinde, Dipak Dattatray; Dambhare, V. Neha; Sharma, Anjali; Mahajan, Chandan; Rath, Arup K. (ACS Applied Nano Materials, 2024)
Strong emission over a wide near-infrared (NIR) region makes lead sulfide quantum dots (QDs) a preferred material in building NIR light-emitting diodes (NIR-LEDs) for numerous applications. Narrow-bandgap emitter QDs blended in the matrix of high-band gap QDs offer a simple yet powerful architectural platform for building high-performance NIR-LEDs. So far, the all-QD-based blend architecture has been realized using a poorly controlled solid-state ligand exchange approach. Advanced solution-phase ligand exchange, which offers greater control over surface passivation, is yet to be realized in all-QD LED device construction. We observe that the solution-phase ligand exchange from the optimized lead halide and thiol ligand combination, used in high-performing QD solar cell construction, is inefficient in realizing efficient all-QD LEDs, which could have restricted the adoption of the solution-phase ligand exchange thus far. Here, we introduce an innovative dual-ligand strategy to build all-QD-based NIR-LEDs using an advanced solution-phase ligand exchange approach. Through ligand engineering of matrix QDs, we managed to improve photoluminescence quantum yield (40%), reduce trap density (10(14) cm(-3)), and prolong carrier lifetime (832 ns). The LED devices benefit from improved electronic properties and balanced carrier injection to yield 6% EQE and 7.7% PCE, which are six times higher than those of state-of-the-art ligands.
Keywords: electroluminescence; lead sulfide; ligand passivation; light-emitting diodes; near-infrared; quantumdots

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Fermi-level equilibrium-driven trap filling in multibandgap PbS quantum dot solids enabling record voltage generation and improved carrier transport in high-performance solar cells - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup Kumar (ACS Energy Letters, 2025)
To leverage the unique optical properties of quantum dots (QDs) in solar cells, it is crucial to address electronic traps from unsaturated surface states of high surface area QDs. Despite advancements in surface passivation, even the best-coupled QD solids exhibit significant sub-bandgap trap states. This study introduces engineered multibandgap PbS QD solids that achieve passivation of deep traps below the conduction band through electron migration from dopant QDs. Our findings indicate that electron flow, driven by Fermi energy balancing in blend films, fills deep trap states, reducing trap density by half and shifting trap energy positions closer to the conduction band. During electrical transport, trap filling minimizes trapping and detrapping events, enhancing overall carrier mobility, despite higher-bandgap dopant QDs not contributing to carrier transport due to their unfavorable energy positions. Improved trap passivation in coupled QD solids leads to a record V oc of 725 +/- 10 meV for the 1.33 eV excitonic peak of QDs and a power conversion efficiency exceeding 14% in solar cells.

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell

Unveiling the reactivity of N-heterocyclic methylene hydrazines - Balayan, Kajal; Biswas, Arindam; Sharma, Himanshu; Tiwari, Prabhakar; Vanka, Kumar; Gonnade, Rajesh G.; Rath, Arup K.; Sen, Sakya S. (Dalton Transactions, 2026)
We present the first reactivity profile of N-heterocyclic methylene hydrazines, revealing distinct competition between steric and electronic control. Reactions with HCl are electronically driven, resulting in protonation at the proximal nitrogen, while the bulky Lewis acid B(C6F5)3 coordinates to the sterically accessible distal nitrogen. Additionally, we demonstrate that these scaffolds undergo spontaneous, base-free HCN elimination with tetracyanoethylene (TCNE) to form highly conjugated molecules with significantly reduced HOMO-LUMO gaps.